Citizenship Policies Between Nation-State Building and Globalisation: Attitudes of the Decision Makers in Estonia - Kalev, Leif; Ruutsoo, Rein (Studies of Transition States and Societies, 2010)
In the following article, we examine the positions of the decision makers of Estonia on multiple and European citizenship. The Estonian case ofers good opportunities to discuss the structuring of the feld of citizenship in the context of a country that is building up a European style nation-state but that has to simultaneously adjust to the changes in statehood usually characterised as globalisation and Europeanisation. The article is based on a survey conducted in 2003-2004 in eight countries: Estonia, Finland, France, Germany, Greece, Israel, Portugal and United Kingdom. We will frst briefy characterise the socio-historical context of Estonian citizenship policies, then discuss the results of the empirical research, relate these to wider trends and draw some conclusions.